Mortality rate and associated factors among patients co-infected with drug resistant tuberculosis/HIV at Mulago National Referral Hospital, Uganda, a retrospective cohort study. - Joan Rokani Bayowa; Joan N Kalyango; Joseph Baruch Baluku; Richard Katuramu; Emmanuel Ssendikwanawa; Jane Frances Zalwango; Rebecca Akunzirwe; Stella Maris Nanyonga; Judith Ssemasazi Amutuhaire; Ronald Kivumbi Muganga; Adolphus Cherop (Public Library of Science (PLoS), 2023)
Drug resistant tuberculosis (DR-TB)/HIV co-infection remains a growing threat to public health and threatens global TB and HIV prevention and care programs. HIV is likely to worsen the outcomes of DR-TB and DR-TB is likely to worsen the outcomes of HIV despite the scale up of TB and HIV services and advances in treatment and diagnosis. This study determined the mortality rate and factors associated with mortality among persons on treatment co-infected with drug resistant TB and HIV at Mulago National Referral Hospital. We retrospectively reviewed data of 390 persons on treatment that had a DR-TB/HIV co-infection in Mulago National Referral Hospital from January 2014 to December 2019.Modified poisson regression with robust standard errors was used to determine relationships between the independent variables and the dependent variable (mortality) at bivariate and multivariate analysis. Of the 390 participants enrolled, 201(53.9%) were males with a mean age of 34.6 (±10.6) and 129 (33.2%,95% CI = 28.7-38.1%) died. Antiretroviral therapy(ART) initiation (aIRR 0.74, 95% CI = 0.69-0.79), having a body mass index (BMI)≥18.5Kg/m2 (aIRR 1.01, 95% CI = 1.03-1.17), having a documented client phone contact (aIRR 0.85, 95% CI = 0.76-0.97), having a mid-upper arm circumference,(MUAC) ≥18.5cm (aIRR 0.90, 95% CI = 0.82-0.99), being on first and second line ART regimen (aIRR 0.83, 95% CI = 0.77-0.89),having a known viral load (aIRR 1.09, 95% CI = 1.00-1.21) and having an adverse event during the course of treatment (aIRR 0.88, 95% CI = 0.83-0.93) were protective against mortality. There was a significantly high mortality rate due to DR-TB/HIV co-infection. These results suggest that initiation of all persons living with HIV/AIDS (PLWHA) with DR-TB on ART and frequent monitoring of adverse drug events highly reduces mortality.